Future Application and Middleware Technology on e-Science - Byeon, Ok-Hwan.; Kwon, Jang Hyuk.; Dunning, Thom.; Cho, Kum Won.; Savoy-Navarro, Aurore; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
As scientific research increasingly requires the efforts of globally diverse, multidisciplinary teams from different laboratories and organizations, there surfaces a need to facilitate this kind of collaborative work. These large-scale scientific initiatives, where information technology plays an important role, are termed e-Science; e-Science activities employ geographically distributed resources like high performance computing facilities, scientific instruments, databases, and high performance networks. Future Application and Middleware Technology on e-Science presents selected papers from the 2008 Korea e-Science All-Hands-Meeting (AHM 2008). Hosted by the Korea Institute of Science and Technology Information (KISTI), the Korea e-Science AHM was designed to bring together developers and users of e-Science applications and enabling information technologies from international and interdisciplinary research communities. The AHM 2008 conference served as a forum for engineers and scientists to present state-of-the-art research and product/tool developments, and to highlight related activities in all fields of e-Science. The following topics concerning e-Science are covered in this volume: e-Science applications in Physics, Astronomy, and Chemistry e-Science applications in Bio-medicine and Life science e-Science applications in Geo-science with remote sensing e-Science applications in Climates and Earth systems e-Science applications in Engineering (Aerospace, Ship, Automobile, and etc) Grid technologies (Computing, Data, VO, and etc) Collaborative science models and techniques Enabling technologies of Workflows and Web services Resource management and scheduling Problem solving environments Scientific data management Application development environments Robust and transparent middleware Programming paradigms and models Software engineering tools Community development and engagement User outreach, training, and documentation The works presented in this edited volume bring together cross-disciplinary information on e-Science in one cohesive source. This book is suitable for the professional audience composed of industry researchers and practitioners of e-Science. This volume is also suitable for advanced-level students in the field.
Web-Based Integrated Research Environment for Aerodynamic Analyses and Design -- An Approach to Integrated Design, Analysis and Data Management for Rapid Air Vehicle Design -- Development of v-DMU Based on e-Science Using COVISE and SAGE -- Design of a Four Degree_of_Freedom Manipulator for Northern Light Mars Mission -- Design and Application of GeoNet System for ABC Cooperative Environment -- Application Architecture of Avian Influenza Research Collaboration Network in Korea e-Science -- York University Space Engineering Nanosatellite Demonstration (YuSend) Mission Development -- A Dynamic Bridge for Data Sharing on e-Science Grid Implementing Web 2.0 Service -- A Grid Middleware Framework Support for a Workflow Model Based on Virtualized Resources -- Grid Workflow-Driven Healthcare Platform for Collaborative Heart Disease Simulator -- An Approach to Multi-Objective Aircraft Design -- Experiences and Requirements for Interoperability Between HTC and HPC-driven e-Science Infrastructure -- Interactive Scientific Visualization of High-resolution Brain Imagery Over Networked Tiled Display -- Object-Oriented Implementation of the Finite-Difference Time-Domain Method in Parallel Computing Environment -- Study on Collaborative Object Manipulation in Virtual Environment -- Protein-Protein Interaction Network and Gene Ontology.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Information systems; Database management; Computer Science; Computer Systems Organization and Communication Networks; Information Systems and Communication Service; Computer Communication Networks; Database Management